Predictive value of achieved blood pressure for cardiac events in the long-term follow-up of heart transplant recipients. Issue 1 (February 2019) - Ambrosi, Pierre; Macé, Loic; Habib, Gilbert
Abstract : Background: A low diastolic blood pressure (DBP) is associated with increased cardiovascular events in patients with coronary artery disease or chronic kidney disease. Aim: The aim of this study was to assess the association of blood pressure with cardiac events during the long-term follow-up of heart transplant recipients. Patients and methods: In this prospective cohort study, we performed ambulatory blood pressure monitoring and home blood pressure monitoring in 76 transplant heart recipients 13.5±6.6 years after transplantation. The patients were followed for 54±17 months after blood pressure monitoring. Results: Twenty-one patients had a cardiac event (cardiac death, acute coronary event, coronary revascularization procedure, and hospitalization for heart failure) during the follow-up. In the Kaplan–Meier survival analysis, we found that a DBP below the median value (<81 mmHg) was associated significantly with cardiac events (log-rank: P =0.01). In a multivariate model, plasma creatinine and left ventricular ejection fraction (LVEF), but not DBP, were associated significantly with cardiac events. Low DBP was associated significantly with LVEF less than 55% ( P =0.004). Conclusion: A DBP below the median value predicts cardiac events during the long-term follow-up of heart transplant recipients, but is not an independent predictor. The association between low DBP and low LVEF explains at least in part the predictive value of low DBP.